Directive Speech Act used by Isabel Conklin in The Summer I Turned Pretty Novel - Dahlan, Nurasisah; Maca, Sudirman; Wahyuni, Rezki Amalia (Humaniora: Journal of Linguistics, Literature, and Education, 2024)
This study investigates the use of directive speech acts by Isabel Conklin in Jenny Han's novel, "The Summer I Turned Pretty." Employing a descriptive qualitative approach, the research focused on identifying and analyzing the types of directive speech acts present in the text. A total of 5 types of directive speech acts were found, categorized into: commanding, requesting, forbidding, inviting, and suggesting. The objectives of the study include understanding how these speech acts reflect Isabel's character and influence her relationships. The results indicated that each type of directive speech act played a crucial role in shaping Isabel's interactions, with commanding speech acts reflecting her need for control, while requesting and inviting speech acts foster cooperation and inclusivity. The study concluded that Isabel's use of directive speech acts significantly contributed to her character development and the dynamics of her relationships throughout the novel.